2006
DOI: 10.1021/bm050971c
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and Fatigue Properties of Polystyrene−Polyisobutylene−Polystyrene, an Emerging Thermoplastic Elastomeric Biomaterial

Abstract: This paper will discuss the biocompatibility and dynamic fatigue properties of polystyrene-b-polyisobutylene-b-polystyrene thermoplastic elastomer with 30 wt % polystyrene (SIBS30), an emerging FDA-approved biomaterial. SIBS30 is a very soft, transparent biomaterial resembling silicone rubber, with superior mechanical properties. Using the hysteresis method adopted for soft biomaterials, the dynamic fatigue properties of SIBS30 were found to be between those of polyurethane and silicone rubber, with fatigue li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 20 publications
1
64
0
3
Order By: Relevance
“…While showing no evidence of in vivo degradation [18], the original thermoplastic SIBS polymer, which was adapted for the PHV application by reinforcing the valve leaflets with Dacron fiber mesh, did exhibit a significant dynamic creep in sheep experiments [25]. The optimized valve was designed around the improved thermoset version of this polymer-xSIBS [19], with the specific goal of reducing its dynamic creep and increasing its tensile strength [27]. This facilitated manufacturing the valve prototypes entirely from xSIBS, using heated compression molding without the reinforcing fiber mesh of the previous design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While showing no evidence of in vivo degradation [18], the original thermoplastic SIBS polymer, which was adapted for the PHV application by reinforcing the valve leaflets with Dacron fiber mesh, did exhibit a significant dynamic creep in sheep experiments [25]. The optimized valve was designed around the improved thermoset version of this polymer-xSIBS [19], with the specific goal of reducing its dynamic creep and increasing its tensile strength [27]. This facilitated manufacturing the valve prototypes entirely from xSIBS, using heated compression molding without the reinforcing fiber mesh of the previous design.…”
Section: Discussionmentioning
confidence: 99%
“…We continue to collaborate with Innovia, who have since developed an improved version of this polymer, xSIBS [19], which is designed to eliminate the significant dynamic creep of thermoplastic SIBS that has limited its utility in PHVs [27]. We have designed a new trileaflet polymeric valve using our device thrombogenicity emulation (DTE) methodology [28,29], which employs state-of-the-art numerical and experimental methods to virtually test and hemodynamically optimize, via an iterative process, blood recirculation medical devices with the goal of eliminating the need for anticoagulants and making the research and design process more efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(styrene-block-isobutylene-block-styrene) (SIBS) copolymer is a thermoplastic elastomer (TPE) that possesses outstanding biocompatibility and generates close to no foreign body reaction when implanted in the human body [1][2][3][4][5][6]. SIBS has a triblock linear structure formed by a block of polyisobutylene between blocks of polystyrene (PS).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, accelerated cyclic fatigue (by tension) has shown that SIBS coated stents maintained physical integrity at low loading levels. SIBS also showed superior fatigue properties compared to silicone and it has been successfully reinforced with polypropylene fibers, further improving fatigue performance [3,11]. However, accelerated cyclic fatigue fails to capture the effects of absorbed fluids on the physical deterioration of the material.…”
Section: Introductionmentioning
confidence: 99%